The Level of a Short Form of Multidrug Resistance-Associated Protein 1 Is Elevated in Plasma Small Extracellular Vesicles Derived From Patients With Pancreatic Ductal Adenocarcinoma - Bhandari, Kritisha; Lu, Madison; Marshall, Gillian; Kong, Jeng Shi; Xu, Chao; Jain, Ajay; Huang, Ying; Hollingsworth, Michael A; Ding, Wei-Qun (The FASEB journal, 2025)
Multidrug resistance-associated protein 1 (MRP1) is an ATP-dependent transmembrane efflux pump that confers drug resistance. MRP1 is overexpressed in pancreatic ductal adenocarcinoma (PDAC) and other malignancies. However, its diagnostic value in cancer has not been explored. The present study examined MRP1 expression in plasma small extracellular vesicles (sEVs) derived from PDAC and colon cancer patients. The human plasma samples were obtained from the NCI-sponsored Cooperative Human Tissue Network, Stephenson Cancer Center, and Oklahoma Blood Institute. sEVs were isolated using double filtration followed by the polymer precipitation method or using ultracentrifugation. Western blotting was performed to evaluate the expression level of MRP1, and proteomics were applied to confirm the detection of a short form of MRP1 in plasma sEVs. A short form of MRP1, representing the region between QCRL-1 and C-terminus domains of the protein, was identified in plasma sEVs, and its level was significantly elevated in plasma sEVs derived from patients with early- and late-stage PDAC, compared with matched healthy subjects (n = 34 for each group). The level of the short form of MRP1 was also elevated in plasma sEVs derived from patients with colon cancer (n = 44) but not in those derived from patients with breast cancer (n = 15). The levels of the short form of MRP1 in plasma sEVs were not related to the chemotherapy status of the patients. We thus conclude that a short form of MRP1 is identified in plasma sEVs and its expression level is significantly elevated in patients with early-stage and late-stage PDAC, irrespective of their treatment status.